2016
DOI: 10.1002/anie.201606531
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III)‐Catalyzed Regioselective Intermolecular Unactivated Secondary Csp3−H Bond Amidation

Abstract: For the first time, a highly regioselective intermolecular sulfonylamidation unactivated secondary Csp(3) -H bond has been achieved using Ir(III) catalysts. The introduced N,N'-bichelating ligand plays a crucial role in enabling iridium-nitrene insertion into a secondary Csp(3) -H bond via an outer-sphere pathway. Mechanistic studies and density functional theory (DFT) calculations demonstrated that a two-electron concerted nitrene insertion was involved in this Csp(3) -H amidation process. This method tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 60 publications
(11 reference statements)
0
34
0
Order By: Relevance
“…Zeng, Ke,a nd co-workers later showed that amide 180 is also ac ompetent substrate for the same transformation with secondary CÀHb onds under similar reaction conditions. [85] As reported by Xia, Shi, and co-workers,t he arylation of primary C À Hb onds can be accomplished with the same directing group and the same Ir precatalyst. [86] Oxime 182 is arylated with diaryliodonium salt 47 to afford 183.…”
Section: Iridium(iii)mentioning
confidence: 84%
“…Zeng, Ke,a nd co-workers later showed that amide 180 is also ac ompetent substrate for the same transformation with secondary CÀHb onds under similar reaction conditions. [85] As reported by Xia, Shi, and co-workers,t he arylation of primary C À Hb onds can be accomplished with the same directing group and the same Ir precatalyst. [86] Oxime 182 is arylated with diaryliodonium salt 47 to afford 183.…”
Section: Iridium(iii)mentioning
confidence: 84%
“…Removal of the tosyl group of 4 was attempted under several conditions (Scheme ). Sonication in the presence of magnesium in methanol (Condition A) gave no reaction, whereas magnesium and titanium isopropoxide with chlorotrimethylsilane (Condition B), and samarium iodide and pyrrolidine in THF/water (Condition C), both resulted in decomposition. Finally, we explored a 3‐step approach involving the addition of a Boc group to N ‐tosylamines which, although having two extra steps, would accomplish the removal of the tosyl group in high yields .…”
Section: Resultsmentioning
confidence: 99%
“…[43] Distinct from the [Cp*M III ]-catalyzed CÀH activation strategy,t hey utilized ab identate directing group to enable an insertion of the sulfonamideg roup into aC ÀH bond, presumably through an outer-sphere pathway.W hen Nbutylpicolinamides that contained a N,N'-bidentate chelating site reacted with sulfonyl azides in the presence of [(Cp*IrCl 2 ) 2 ] and AgBF 4 ,t he g-selective C(sp 3 )ÀHa midationp roduct was obtained in DCE at 60 8C( 24 h). [43] Distinct from the [Cp*M III ]-catalyzed CÀH activation strategy,t hey utilized ab identate directing group to enable an insertion of the sulfonamideg roup into aC ÀH bond, presumably through an outer-sphere pathway.W hen Nbutylpicolinamides that contained a N,N'-bidentate chelating site reacted with sulfonyl azides in the presence of [(Cp*IrCl 2 ) 2 ] and AgBF 4 ,t he g-selective C(sp 3 )ÀHa midationp roduct was obtained in DCE at 60 8C( 24 h).…”
Section: Càhinsertionmentioning
confidence: 99%
“…Recently,K e, Zeng, and co-workers reported a[ Cp*Ir III ]-catalyzed amidationr eaction of unactivated secondary C(sp 3 )ÀH bonds (Scheme 32). [43] Distinct from the [Cp*M III ]-catalyzed CÀH activation strategy,t hey utilized ab identate directing group to enable an insertion of the sulfonamideg roup into aC ÀH bond, presumably through an outer-sphere pathway.W hen Nbutylpicolinamides that contained a N,N'-bidentate chelating site reacted with sulfonyl azides in the presence of [(Cp*IrCl 2 ) 2 ] and AgBF 4 ,t he g-selective C(sp 3 )ÀHa midationp roduct was obtained in DCE at 60 8C( 24 h). The optimized reaction conditions weres uccessfully applied to the reaction of av ariety of N-alkyl-substituted picolinamides with sulfonyl azides.…”
Section: Càhinsertionmentioning
confidence: 99%